2021
DOI: 10.1111/resp.14059
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of bronchiectasis in Korea: First data from the Korean Multicentre Bronchiectasis Audit and Research Collaboration registry and comparison with other international registries

Abstract: Understanding the aetiology and characteristics of patients with bronchiectasis is vital for developing strategies to reduce the burden of disease; however, geographical variations in these characteristics, which may have important implications for diagnosis and treatment, 1,2 make it difficult to formulate a uniform strategy for investigation. Here, we describe the burden of illness and treatment among Korean bronchiectasis patients and compare the results with those from three geographically and ethnically d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 4 publications
0
32
0
Order By: Relevance
“…Exclusion criteria were as follows: (1) bronchiectasis due to cystic fibrosis; (2) traction bronchiectasis associated with interstitial lung disease; (3) patients being actively treated for pneumonia, pulmonary TB, or non-tuberculous mycobacteria (NTM) infection; (4) patients who were unable or unwilling to provide informed consent; and (5) pregnant patients. The detailed registry protocol and baseline characteristics of the patients were described previously [3,6].…”
Section: Study Design and Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exclusion criteria were as follows: (1) bronchiectasis due to cystic fibrosis; (2) traction bronchiectasis associated with interstitial lung disease; (3) patients being actively treated for pneumonia, pulmonary TB, or non-tuberculous mycobacteria (NTM) infection; (4) patients who were unable or unwilling to provide informed consent; and (5) pregnant patients. The detailed registry protocol and baseline characteristics of the patients were described previously [3,6].…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…The increased prevalence of bronchiectasis has led to the establishment of several prospective multicentre bronchiectasis registries [3][4][5]. Research from the international registries revealed that the aetiologies of bronchiectasis varied according to region, and tuberculosis (TB) was most common in Asian countries, including India and South Korea [6,7]. Therefore, elucidating specific clinical characteristics of patients with post-TB bronchiectasis is essential to successfully manage Asian patients with bronchiectasis.…”
Section: Introductionmentioning
confidence: 99%
“…Bronchiectasis itself can cause obstructive ventilatory impairment (31). The high rate of COPD can be also attributable to the relatively high prevalence of asthma and TB in this cohort (14). The current Global Initiative for Chronic Obstructive Lung Disease (GOLD) recommendations indicate asthma or TB as a risk factor of COPD (32).…”
Section: Discussionmentioning
confidence: 97%
“…The Korean Multicenter Bronchiectasis Audit and Research Collaboration (KMBARC) is a prospective, observational study of bronchiectasis in Korea (13,14). The KMBARC uses the Korean version of the Bronchiectasis Health Questionnaire (BHQ) for QoL measurement (15), which has the advantage of simplicity over other QoL measurements for bronchiectasis.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence and disease burden of bronchiectasis has increased worldwide [ 3 - 6 ], including South Korea [ 1 , 7 - 9 ]. One of the obstacles to adequately addressing the disease burden of bronchiectasis is its heterogeneity [ 10 , 11 ], as it may be caused by or related to various respiratory or systemic diseases [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%